Long-term efficacy of denture cleansers in preventing Candida spp. biofilm recolonization on liner surface - Ana Paula Coelho Vieira; Plínio Mendes Senna; Wander José da Silva; Altair Antoninha Del Bel Cury (Sociedade Brasileira de Pesquisa Odontológica, 2010)
This study evaluated the long-term efficacy of denture cleansers against Candida spp. biofilm recolonization on liner surface. Specimens were fabricated of a poly(methyl methacrylate)-based denture liner and had their surface roughness evaluated at baseline and after cleansing treatments. C. albicans or C. glabrata biofilms were formed on liner surface for 48 h, and then the specimens were randomly assigned to one of cleaning treatments: two alkaline peroxides (soaking for 3 or 15 min), 0.5% sodium hypochlorite (10 min) or distilled water (control; 15 min). After the treatments, the specimens were sonicated to disrupt the biofilm, and residual cells were counted (cell/mL). Long-term effectiveness of the cleaning processes was determined by submitting a set of cleaned specimens to biofilm growth conditions for 48 h followed by estimation of cell counts. The topography of specimens after cleaning treatments was analyzed by SEM. Data were analyzed by ANOVA and Tukey's test (α; = 0.05). Results of cell count estimation showed significant differences in cleanliness among the treatments (p < 0.001), and it could be observed by SEM. However, no significant difference (p > 0.05) was observed among the Candida species regarding the recolonization condition. Alkaline denture cleansers showed similar cleaning performance and both differed from the control (p < 0.001). Sodium hypochlorite was the only treatment that removed biofilm efficiently, since no viable cells were found after its use. In conclusion, alkaline peroxide denture cleansers were not effective in removing Candida spp. biofilm from denture liner surfaces and preventing biofilm recolonization.